A Model Perspective Explanation of the Long-Term Sustainability of a Fully Human BCMA-Targeting CAR (CT103A) T-Cell Immunotherapy - Mu, Wei; Long, Xiaolu; Cai, Haodong; Chen, Caixia; Hu, Guang; Lou, Yaoyao; Xing, Shugang; Wang, Di; Wang, Jue; Xiao, Min; Wang, Kun; Sun, Zhongyi; et al. (Frontiers in Pharmacology, 2022)
Different from canonical drugs, CAR T-cells are “living drugs”, which derived from patient’s own blood. Studies of the pharmacokinetics of CAR T-cells could improve our understanding of their efficacy, safety, optimal dosage, and other characterizes. We previously reported a phase I study of a novel fully human BCMA-targeting CAR (CT103A) in 18 patients with relapsed/refractory multiple myeloma. CT103A exhibited extraordinary persistence with low anti-drug antibody positivity. To figure out the pharmacokinetic characterizes and investigate the potential reason of CT103A’s long-term persistence, we established a population pharmacokinetic (PopPK) model of CT103A based on 18 patients cohort by applying nonlinear mixed-effects modeling and analyzed the CAR T-cell clonal evolution. The results suggested that extramedullary spreading was found to impair Cmax and was therefore added as a covariate to the modified model. The model revealed tocilizumab and corticosteroids showed no impact on the CT103A expansion rate. No dominant clone existed in patients with persistently high peripheral CT103A by CAR integration sites analysis. Finally, patients with lower contraction rate constants and higher Cmax as well as memory CT103A fraction could achieve better clinical responses. Taken together, this study developed a PopPK model of a fully human anti-BCMA CAR T-cell therapy, and summarized its model characteristics. We suggested that the long-term persistence of CT103A was attributed to the memory CAR T-cell fraction but not the clonal evolution. This study will improve people’s understanding of pharmacokinetics and PopPK of CAR T-cell immunotherapy.